Determination of diagnostic reference level (DRL) on computed tomography (CT) non contrast examination - Mulyati Sri; Rasyid Rasyid; Daryati Siti; Latifah Leny (E3S Web of Conferences)
Monitoring patient doses on CT Scans in hospitals very important, it must be monitored periodically especially in DRL monitoring of CT Examination. There is still a need for socialization regarding the need for radiation monitoring of high dose radiation in CT Scan used. The DRL was related to efforts to optimize radiation protection must be monitored periodically on CTDI Vol and DLP for lowest possible dose and optimum image quality results. Determination of DRL values from 75% percentile from recording mean CTDI vol and total DLP MSCT examination of head and abdomen non-contrast. The overall results obtained from the Head MSCT examination DRL as follows: DRL on CTDI Vol from Quarters I-IV obtained 63.45 mGy, exceeding the standards IDRL requirement of 60 mGy. Meanwhile, DRL in DLP Total from Quarters I-IV was 1005.05-1096.45 mGy.cm which was lower than IDRL 1275 mGy.cm. Meanwhile, the results of the DRL on theAbdominal MSCT are as follows: Quarter I-IV is 9.35-10.31 mGy below the IDRL that was17 mGy. Meanwhile, local DRL from QuartersI-IV obtained: 401.34 - 428.73 mGy.cm below IDRL which was 885 mGy.cm, its suitable with Decree of the Head of Bapeten Number 1211/K/V/2021.